Teladan PELSUS Dalam Membangun Iman Jemaat di Jemaat GMIM Torsina Tumumpa - Tiho, Leonardo Christian (Educatio Christi, 2022)
Setting a good example turns out to play a very important role in life. This role can have an influence on something central, namely faith. Therefore, in setting a good example, it must be done sincerely. So in realizing it all, an example is needed. Through a good example, it can have a good influence, but if on the contrary it will bring something bad. presbiter especially elders and deacons play an important role in setting an example for their congregations. So for that reason the presbiter must realize that the example will always play an important role in building the faith of the congregation to be better.The aim of the study is to highlight and describe the presbiter exemplary criteria. To highlight and describe the example of presbiter in building the faith of the congregation in the GMIM Torsina Tumumpa congregation. To highlight and describe the example of PELSUS and the faith growth of the congregation at GMIM Torsina Tumumpa.The research method used is a qualitative method with a descriptive approach. Data collection techniques used is interviews, field observations and literature studies.From the results of the research found in the research field, it concerns the presbiter Example in building the faith of the congregation that PELSUS there, especially the elders and deacons, have understood what a good example is. Although there are also those who do not realize the importance of example, they try to realize it to build the faith of the congregation. The PELSUS are also still full of limitations so that there are still mistakes in their attitude to set an example but these shortcomings do not become a stumbling block to continue to improve themselves. So that from the presbiter to the church members have hope in the faith growth of the congregation in the future so that the presbiter are more serious in setting an example to build the faith of the congregation and the congregation can give themselves more in service to God.